Social branding and think tanks in the banking sector in Spain - Miguel Ángel Nicolás Ojeda; César San Nicolás Romera; Pedro A. Hellín Ortuño (Frontiers in Political Science)
IntroductionThis paper offers a study of branding strategies in the Spanish banking sector, focusing on corporate narratives of a social nature and their relationship with the ideas and trends proposed by Spanish think tanks specialising in the sector. Based on the evolution observed in brand communication strategies following the 2007 economic crisis, we aim to study the redefinition of a new commercial and social narrative for banks through formats and mechanisms that encourage interaction within digital communication ecosystems.MethodologyTo carry this out, we have outlined three phases: In the first phase, we will analyse the socially-oriented advertising and corporate communication actions of the six main banking brands. In the second phase, we will review the communication of Spanish think tanks specialising in the banking sector. In the third phase, we will identify and classify by theme the social ideas proposed by these think tanks through their news sections, trend reports, and corporate audiovisual content, in order to determine whether there is a direct relationship with the corporate proposals of the banking brands analysed.Results and discussionThe results of the analysis describe a promotional aesthetic of a discourse in Spanish banking that appropriates the commitment to social progress, displaying traits of similarity with those planned by Think tanks.